Ekstensifikasi Penentuan Outsider Pada Pengungkapan Kejahatan Insider Trading di Pasar Modal Berdasarkan Pendekatan Misappropriation Theory - Daffa Alfandy, Muhammad (Zaaken: Journal of Civil and Business Law, 2024)
The paradigm used in setting insider trading in the Capital Market Law adheres to the principle of fiduciary duty. That is, conceptually, company insiders as parties entrusted to carry out company operations are obliged to exercise the trust in good faith, so that the insider is not allowed to utilize the ownership of material information to conduct securities transactions aimed at benefiting himself. The problem arises when the principle of fiduciary duty adopted by the Capital Market Law cannot disclose insider trading conducted by: (1) outsiders or tippees who obtain inside information from outsiders or other tippees and (2) outsiders or tippees who obtain material information without unlawful. This is because the burden of proof on the fiduciary duty principle is the relationship between the perpetrator and insiders in the issuer. The Capital Market Act should open up space for the use of misappropriation theory whose approach is oriented towards the ownership nature of material information as applied by Singapore. The research method used is juridical-normative using a statutory approach, a comparative approach, and a case approach. The results showed that the principle of fiduciary duty as embodied in Capital Market Law cannot reach the behavior of secondary tippees and tippees who obtain information without violating the law. Therefore, the author argues that it is necessary to extensify the outsider determination based on misappropriation theory.